Rumah Baca Pustaka Bunda Haz Dalam Menumbuhkan Minat Membaca Masyakarat Dusun Genengan Kecamatan Sukorejo Kabupaten Pasuruan - Mukarromah; Aminah, Lilik (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to describe the role of Rumah Baca Pustaka Bunda HAZ in growing the Reading Interest of the Genengan Hamlet Community, Sukorejo District, Pasuruan Regency and its supporting and inhibiting factors. The type of research used is qualitative research with a descriptive approach. The results showed that the Bunda HAZ Library Reading House was a house containing various books and educational toys belonging to one of the residents who played a very important role in fostering public interest in reading. It was proven that before the Bunda HAZ Library Reading House, people did not think that reading was important. Even among children, reading only when at school and doing homework at home. The rest of the children play, watch television and cell phones. When Rumah Baca Pustaka Bunda HAZ was present in their midst by presenting a variety of interesting educational books and toys, some of them were enthusiastic to read. The supporting factors are facilities in the form of interesting educational books and toys, the comfort of the place and good service from the manager. While the inhibiting factor is the lack of guards so that service time is limited and the state conditions in the pandemic era limit visits to the Bunda HAZ Library Reading House.Keywords: Reading House, Interests, and Society.